Evangelicals and Presidential Politics : From Jimmy Carter to Donald Trump - Moore, Andrew S., 1968- (Book collections on Project MUSE., 2021)
"Using a 1976 Newsweek cover story on the emerging politicization of evangelical Christians as a starting point, the contributors to "Evangelicals and Presidential Politics" engage the scholarly literature on evangelicalism from a variety of angles to offer new answers to persisting questions about the movement. The volume starts with the question of when evangelical political influence began and what its motivating impulses were. The standard historical narrative describes the period between the 1925 Scopes Trial and the early 1970s as a silent one for evangelicals. In that narrative, when they did re-engage in the political arena, they did so over abortion. Chapters by Randall Stephens and Randall Balmer challenge that narrative. Stephens moves the starting point up earlier in the twentieth century, and Balmer looks closely at the words and actions of leaders to conclude that race, not abortion, motivated activists. In his examination of the relationship between African Americans and evangelicalism, Dan Wells uses a sidebar in the Newsweek story on black activist Eldridge Cleaver, a born-again Christian, to illuminate the former Black Panther's uneasy relationship with white evangelicals. Issues of gender and sexuality were central to the evangelical political mobilization of the 1970s, but despite a recent spate of monographs on the mobilization of the Christian Right, the process by which evangelicals made these issues a focus remains not fully understood. Chapters by Daniel K. Williams, Allison Vander Broek, and J. Brooks Flippen explore the relationship between evangelicals and the anti-abortion movement as well as the political ramifications of their anti-abortion stance. The election of 1976 helped to politicize abortion, a development that encouraged a realignment of political alliances and altered evangelicals' expectations for political candidates, a consequence that continues into the twenty-first century. Also, in 1976, Foy Valentine, leader of the Southern Baptist Christian Life Commission, distinguished the South's brand of Protestant Christianity from the evangelicalism described by Newsweek. Despite Valentine's efforts to prevent it, however, Southern Baptists quickly became associated with the evangelicalism of the Religious Right and the South's shift to the Republican Party. Jeff Frederick discusses that politicization from the 1970s into the twenty-first century, suggesting that southern religiosity has suffered as a result because southern evangelicals surrendered their authenticity and adopted a moral relativism that they criticized in others. Continuing into the twenty-first century, Ward Holder and Hannah Dick examine political evangelicalism in the wake of Donald Trump's election. Holder's examination lays bare the compromises that many Southern Baptists had to make to justify their support for Trump, a candidate who did not share their religious or moral values. Hannah Dick focuses on media coverage of Trump's 2016 campaign and contends that major news outlets misunderstood Trump's relationship to evangelicals and those evangelicals' relationship to politics in general. The result, she suggests, was that the media severely miscalculated Trump's chances of winning the election"--